Drama in the music of Franz Schubert - Davies, Joe (Musicologist); Sobaskie, James William, 1956- (The Boydell Press, 2019)
It is commonly assumed that Franz Schubert (1797-1828), best known for the lyricism of his songs, symphonies, and chamber music, lacked comparable talent for drama. Challenging this view, Drama in the Music of Franz Schubert provides a timely re-evaluation of Schubert's operatic works, while demonstrating previously unsuspected locations of dramatic innovation in his vocal and instrumental music. The volume draws on a range of critical approaches and techniques, including semiotics, topic theory, literary criticism, narratology, and Schenkerian analysis, to situate Schubertian drama within its musical and cultural-historical context. In so doing, the study broadens the boundaries of what might be considered 'dramatic' within the composer's music and offers new perspectives for its analysis and interpretation. Drama in the Music of Franz Schubert will be of interest to musicologists, music theorists, composers, and performers, as well as scholars working in cultural studies, theatre, and aesthetics.